2006
DOI: 10.1159/000093459
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Subjects Aged 75 Years or Over within the PAQUID Cohort: Prevalence and Burden by Severity

Abstract: Background/Aims: To analyze the prevalence of dementia by severity and to describe the sociodemographic characteristics of people with dementia in the community, as well as the consequences of this disease in terms of disability and institutionalization. Methods: This study was based on the PAQUID community-based cohort study of 1,461 subjects aged 75 years or over. Severity of dementia was assessed using the Mini-Mental State Examination (MMSE). Results: The prevalence of dementia was estimated to be 17.8%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 60 publications
2
42
0
4
Order By: Relevance
“…The EURODEM study reported an age-standardized prevalence of dementia of 6.4% [3]. For France, prevalence rates vary between 9.2% for elderly subjects >70 years and 17.8% for those >75 years of age [4,5,6]. Recently published projections show that the number of individuals suffering from Alzheimer dementia in the USA will nearly triple between 2010 and 2050 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The EURODEM study reported an age-standardized prevalence of dementia of 6.4% [3]. For France, prevalence rates vary between 9.2% for elderly subjects >70 years and 17.8% for those >75 years of age [4,5,6]. Recently published projections show that the number of individuals suffering from Alzheimer dementia in the USA will nearly triple between 2010 and 2050 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among these cases, two thirds live in low-income and middle-income countries [1]. Almost half of community-dwelling patients and 59.6% of institutionalized residents with dementia are in moderate or severe stages of this disease [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on the PAQUID cohort study of 1461 subjects aged 75 years or over, the prevalence of dementia was estimated to be 17.8% of this population and Alzheimer's disease was the main etiology of dementia (79.6 per cent) 1.…”
Section: Introductionmentioning
confidence: 99%